Winter‐responding proxy temperature reconstructions and the North Atlantic Oscillation. Issue 11 (10th June 2014) - Jones, P. D.; Harpham, C.; Vinther, B. M.
Abstract Instrumental temperature data for the Northern Hemisphere (30°–90°N) clearly indicate that winter season variability is larger than equivalent measures for summer. This should not be surprising as temperatures in winter are dominated by variability caused by changes in atmospheric circulation features, whereas in summer variability is more dominated by local changes in cloudiness. Here we consider most of the few winter‐responding annually resolved proxy reconstructions of temperature from the northern North Atlantic and northwestern European regions. We find the expected out‐of‐phase relationship between northwest Europe and Greenland due to the North Atlantic Oscillation (NAO), which is stronger when the series from the two locations are formed from more than one series. On 30 year time scales this relationship between the two locations shows no century‐scale variations since 1250 CE (Common Era), the start of our reconstructions, in contrast to the strong positive NAO values before 1400 CE implied by the study of Trouet et al. (2009).